Increased seawater temperature increases the abundance and alters the structure of natural Vibrio populations associated with the coral Pocillopora damicornis - Tout, Jessica; Siboni, Nachshon; Messer, Lauren F.; Garren, Melissa; Stocker, Roman; Webster, Nicole S.; Ralph, Peter J.; Seymour, Justin R. (Frontiers in Microbiology, 2015)
Rising seawater temperature associated with global climate change is a significant threat to coral health and is linked to increasing coral disease and pathogen-related bleaching events. We performed heat stress experiments with the coral Pocillopora damicornis, where temperature was increased to 31°C, consistent with the 2–3°C predicted increase in summer sea surface maxima. 16S rRNA amplicon sequencing revealed a large shift in the composition of the bacterial community at 31°C, with a notable increase in Vibrio, including known coral pathogens. To investigate the dynamics of the naturally occurring Vibrio community, we performed quantitative PCR targeting (i) the whole Vibrio community and (ii) the coral pathogen Vibrio coralliilyticus. At 31°C, Vibrio abundance increased by 2–3 orders of magnitude and V. coralliilyticus abundance increased by four orders of magnitude. Using a Vibrio-specific amplicon sequencing assay, we further demonstrated that the community composition shifted dramatically as a consequence of heat stress, with significant increases in the relative abundance of known coral pathogens. Our findings provide quantitative evidence that the abundance of potential coral pathogens increases within natural communities of coral-associated microbes as a consequence of rising seawater temperature and highlight the potential negative impacts of anthropogenic climate change on coral reef ecosystems.